A case study of typhoon‐induced gravity waves and the orographic impacts related to Typhoon Mindulle (2004) over Taiwan. Issue 18 (19th September 2015) - Wu, J. F.; Xue, X. H.; Hoffmann, L.; Dou, X. K.; Li, H. M.; Chen, T. D.
Abstract: Atmospheric gravity waves (GWs) significantly influence global circulation. Deep convection, particularly that associated with typhoons, is believed to be an important source of gravity waves. Stratospheric gravity waves induced by Typhoon Mindulle (2004) were detected by the Atmospheric Infrared Sounder (AIRS). Semicircular GWs with horizontal wavelengths of 100–400 km were found over Taiwan through an inspection of AIRS radiances at 4.3 μm. Characteristics of the stratospheric gravity waves generated by Typhoon Mindulle were investigated using the Weather Research and Forecasting (WRF) model. The initial and boundary data were determined by the high‐resolution European Center for Medium‐Range Weather Forecasts reanalysis data. The WRF simulation reproduces the main features of Typhoon Mindulle and the significant GWs. The simulated GWs with horizontal wavelengths of 100–400 km match the AIRS observations: they propagate upward and eastward, and the westward components are mostly filtered in the stratosphere. By comparing the measured waves with a WRF simulation in the absent of orography (WRF‐FLAT), we find that the orographic gravity waves (OGWs) generated by the flow of Typhoon Mindulle over the Central Mountain Range (CMR) in Taiwan account for approximately 50% of the total wave momentum flux in the troposphere. The dominant orientation of the OGW wave fronts is parallel to the CMR rideline. When entering into the stratosphere, OGW propagation is determined by the position of the typhoon center relative to the CMR. Key Points: Typhoon‐induced GWs were studied by AIRS observation and WRF simulation The characteristic of TGW and OGW was investigated using WRF Orographic impact on GWs was estimated using a WRF‐FLAT simulation